Correlation between History of Exclusive Breastfeeding and Fine Motoric Development in Children Aged 24-48 Months - Arien Daning Astiti (Fetus : Journal of Midwifery, 2023)
Fine motor development is a skill that involves the coordination of hand, eye, nerve and brain movements which are influenced by several factors, one of which is the child's health and nutrition. This study analyzed the relationship between history of exclusive breastfeeding and fine motor development in children aged 24-48.The population of this study were 40 children and a sample of 36 respondents using the simple random sampling technique. Using a history of exclusive breastfeeding questionnaire and KPSP and analyzed using Fisher's exact test. Research with cross sectional design conducted at Posyandu Manggis 4 Arjasa Village, Jember Regency. The results of the study showed that 72.2% had a history of non-exclusive breastfeeding and 27.8% were exclusively breastfed. Fine motor development according to 72.2% and doubtful 27.8%. The results of the analysis obtained a value of 0.689 or >α0.05, there is no relationship between a history of exclusive breastfeeding and fine motor development in children aged 24-48 months at Posyandu Manggis 4 Arjasa Village. Children's fine motor development cannot be measured from a history of exclusive breastfeeding alone, there are other factors that can support such as mother's education, family income, and history of term gestational age. Mothers are advised to participate in posyandu activities regularly to monitor the growth and development of their children and increase their motivation to provide